(untitled) (Iraqi Journal of Medical Sciences, 2022)
The emergence of multidrug-resistant (MDR) Mycobacterium tuberculosis (Mtb) strains, identified as resistant to at least isoniazid and rifampin, these two drugs form the backbone of the first line drug which is used for tuberculosis (TB) treatment, unresponsive has hampered TB control. As a result of the nearly universal calculation of with half a million new cases of MDR/first line drug TB per year, it is important to keep the database up to date awareness of the processes that contribute to the emergence of MDR Mtb. This resistance is produced for a variety of reasons, including genetic, microbiological factors, non-adherence to treatment by patients and/or failures in therapy administration by some referrer medical centre for TB. This review offers a detailed summary of genetic mechanisms that lead to resistant to first line drug therapy used in management of TB as well as up-to-date information on some new aspects lead to such problem. Keywords: Mycobacterium tuberculosis, first line drug, anti-TB treatment, World Health Organization, isoniazid and rifampin Citation: Hassan JS, Al-Tamimi BJ, Abdulrahman TR, Jamal QW. Resistance mechanisms to first line drug in Mycobacterium tuberculosis: A review. Iraqi JMS. 2022; 20(1): 35-43. doi: 10.22578/IJMS.20.1.5